New media use among youth in Malaysia: a media dependency theory perspective - Mohamed Nawi, Nul Widaya; AlSagoff, Syed Agil; Osman, Mohd Nizam; Abdullah, Zulhamri (PalArch Foundation, 2020)
Purpose-This paper aims to provide an explanation of new mediauseamong youth by building a conceptual framework that related with the Media Dependency Theory. In Malaysia, public concerns continue to rise about the risk of excessive new mediause among youths. Provides on the conceptual model perspective with the origins of the theory in Media Dependency Theory.This paper applies Media Dependency Theory to study the useof the new mediaamongyouthin Malaysia. Researcher are watching the phenomenon among youth in the use of new media is different from most users of developing countries where the new media is the infrastructure has been well built. In Malaysia, wireless networks are in use and Facebook is the main social media widely accepted by users for communication, marketing, and identity building. Through the Media Dependency Theory lens, researcher can see the use of new media from a media perspective where the media plays a role in this society. Malaysia's social background is unique, therefore, themedia use is completely differentfrom what is observed in western countries and researcher conclude some of the consequences of unwanted new media use that goes beyond the scope of knowledge.Design/methodology/approach–The paper is conceptual, and a model is developed as a result of an extensive critical multidisciplinary literature review.Findings -The findings of this study identifynew media use, namely effect and the influence of new mediaand related to the Media Dependency Theory. In addition, the study highlights the potentialfor a positive relationship between the use of new media and youth. One integrative concept frameworks and detailed summary are presented in the paper.